PENERAPAN MODEL ACTIVE KNOWLEDGE SHARING PADA PEMBELAJARAN MATEMATIKA (PENELITIAN EKSPERIMEN PADA MATA PELAJARAN MATEMATIKA DI KELAS V SDN 10 SUNGAI SAPIH KOTA PADANG) (Jurnal Pelangi : Research of Education and Development, 2015)
Students learn mathematics because of fear of the teacher and it is not at the instigation of curiosity. So, students only orient on the final result, not on the process. To make students interested in following the teaching of mathematics, the mathematics learning should be implemented in a way that is interesting, fun, and engaging students actively. If this problem keeps going on, the result in the student learning outcomes is under the minimum completeness criteria (<75). One way that can be proposed by the teacher is applying the AKS Model in Math learning of Class V SDN 10 Sungai Sapih, Padang. Formulation of the problem of this research is whether the mathematics learning outcomes of students taking AKS learning model is better than the mathematics learning outcomes of students taking the conventional learning model or not. This research included experimental research with the research design is Randomized Control Group Only Design. The population was fifth grade students enrolled in the academic year 2014/2015 a total of four classes (161 people). Sampling technique was conducted by drawing numbers, then class experiment was Vc and the control class was Vd. The final test result data processing was conducted through hypothesis testing using t-test. After calculation, it is found that t count> t table (2.915> 1.66), it indicates that the hypothesis is accepted. This means that the learning outcomes of students taking AKS learning model is better than the mathematics learning outcomes of students taking the learning to conventional models.